"It is the fear of exercise that stops me" – attitudes and dimensions influencing physical activity in pulmonary hypertension patients. (1st November 2021) - McCormack, Ciara; Cullivan, Sarah; Kehoe, Brona; McCaffrey, Noel; Gaine, Sean; McCullagh, Brian; Moyna, Niall M.; Hardcastle, Sarah J.
Abstract : Pulmonary hypertension is a progressive cardiorespiratory disease that is characterized by considerable morbidity and mortality. While physical activity can improve symptoms and quality of life, engagement in this population is suboptimal. The aim of this study was to explore attitudes towards exercise and the dimensions that influence physical activity participation in individuals with pulmonary hypertension. Virtual, semi‐structured interviews were conducted with individuals, with a formal diagnosis of pulmonary hypertension. Participants were recruited through the Pulmonary Hypertension Association of Ireland. Interviews were transcribed and analysed using thematic analysis. Nineteen patients were interviewed (n = 19). There was a female preponderance (n = 13) and the mean age was 50 ± 12 years. Three themes were identified and included fear, perceived value of exercise and environmental factors. Fear was the primary theme and included three sub‐themes of fear of (i) over‐exertion, (ii) physical damage and (iii) breathlessness. The perceived value of exercise encompassed two distinct sub‐themes of perceived (i) exercise importance and (ii) benefits of exercise. Environmental factors included the terrain, weather conditions and location. Fear of overexertion, harm and dyspnoea strongly influenced attitudes to and engagement in physical activity. This study revealed heterogenous patient perspectives regarding the importance of physical activity and exercise. Future interventions that mitigate fear and promote the value of physical activity for individuals with pulmonary hypertension may have considerable benefits in promoting physical activity engagement. Such interventions require multidisciplinary involvement, including specialised pulmonary hypertension clinicians and exercise and behaviour change specialists.